O futebol Munduruku : um jogo estratégico nas relações interétnicas e interculturais em Juara-MT - Nascimento, Ronaldo do (2015)
This work is result of a research developed in Federal University of Mato Grosso, at the Post-graduation Programme for a Master's degree in Education, by the research line Social Movements, Popular Education and Public Policies under the theme Education and Indigenous People. The research brings sport, education and sport and leisure public policies into debate, linked to the practice of soccer, by using as reference this social practice, present on Munduruku people, in Nova Munduruku village, located in the Indigenous Land Apiaká/Kayabi in Juara. The goal is to present soccer as a mediator, strategic instrument on the game manifested in the intercultural education field, in Mato Grosso's interethnic context. Soccer, in this context, assumes shapes of a game understood inside and outside of such interethnical context, where the indigenous also live with the inhabitants who live in the urban and rural area of Juara. This practice, marked by Munduruku corporality, begins ludicly of the ball playing with relatives and it goes on its trajectory to the institutionalized form, on soccer which takes place on the official championship, institutionalized. For comprehension of soccer as social practices of these subjects, data qualitative analysis was measured within documents, interviews with the participants and the other's observation, the Munduruku body in movement. We adopted the interpretativity as means of meaningful reading by means of ethnography to best describe the environment of study, whose analysis was measured in humen sciences', education's and physical education's references, in order to weave an understanding of what has been thought, seen and lived in the intercultural context with the indigenous consolidated by the research.